Psychometric Properties and Factor Structures of the CERQ, DERS, and RESE Measures: A Bifactor Approach. Issue 6 (2nd November 2021) - Xu, Lingling; Cheng, Fangyan; Liu, Chutong; Jin, Ruyi; Pan, Hui; Zhang, Minqiang; Liang, Zhengyan
Abstract: This study aims to simultaneously compare the psychometric properties and examine the factor structures of 3 emotion regulation (ER) strategy scales using a bifactor approach. Due to good reliability and validity, extensive use, and the same scoring method, the Cognitive Emotion Regulation Questionnaire, Difficulties in Emotion Regulation Scale, and Regulatory Emotional Self-Efficacy Scale were used to assess ER strategies in 1, 036 Chinese respondents. A bifactor confirmatory factor analysis was designed to address the multidimensionality of the factor structure, and the corresponding bifactor structures were then applied in a subsequent bifactor multidimensional item response theory (MIRT) analysis. Finally, bifactor MIRT was used to compare the psychometric properties of the 3 measures. The results indicated that bifactor structures were appropriate for the 3 ER strategy measures, which performed well overall. Different measures provide the highest accuracy for specific groups and designs. Some strengths and limitations of this article are discussed.